Demographischer Wandel: Modellvorhaben der Raumordnung als Handlungsfeld des Bundes - Gatzweiler, Han-Peter; Kocks, Martina (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
Spatial planning and the bodies responsible for the provision of public amenities / infrastructure services must adapt early and to regionally different extents to a general population decline, to ageing and to the internationalisation of the population. The adaptation requirements resulting from the spatial dimension of demographic change call for a positioning of spatial planning: starting with an examination of spatial planning models and objectives with open results, for instance the maintenance of the postulate of equivalent living conditions, to an examination of the procedures and instruments to fulfil the co-ordination task of spatial planning at the different spatial levels. Demonstration projects also play an important role as an action area of the Federal Government. They provide the opportunity to develop and test innovative policy approaches of spatial planning in collaboration with local protagonists in the regions. The article presents the current demonstration projects of spatial planning in the thematic focus “Infrastructure and Demographic Change” and reports on first results. Strategies and concepts to safeguard an appropriate regional supply of infrastructure are in the centre of interest in this context.